Composite thermal insulation material for lunar building and preparation method of composite thermal insulation material
By using a composite structure of reflective film, honeycomb core, and aerogel layer, combined with a buffer frame design, the problems of low thermal conductivity, high reflectivity, lightweight, and impact resistance of lunar building insulation materials in extreme environments have been solved, achieving long-life insulation performance.
Patent Information
- Application Number
- CN202610138681.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-31
- Publication Date
- 2026-03-17
AI Technical Summary
Existing lunar building insulation materials cannot simultaneously meet the requirements of low thermal conductivity, high reflectivity, lightweight, impact resistance, and long lifespan, and cannot adapt to the extreme thermal cycling and micrometeorite impacts of the lunar environment.
A composite thermal insulation material suitable for lunar architecture was prepared by using a composite structure consisting of a reflective film layer, a honeycomb core layer, and an aerogel layer. The chemical bonding layer achieves low thermal resistance and high stability at the interface, and the displacement compensation function of the buffer frame is combined with this structure.
It achieves efficient heat insulation in the extreme lunar environment, while also being lightweight and impact-resistant, extending service life and meeting the needs of long-term stays.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to aerospace building materials, in particular to a composite thermal insulation material suitable for lunar buildings and a preparation method thereof. BACKGROUND
[0002] With the deep space exploration of human beings towards the normalization of residence on the moon, the construction of lunar buildings has become a key issue, and the thermal insulation system as a core component to ensure the operation of internal equipment and personnel activities of the building directly determines the reliability and practicality of the lunar building. However, the lunar surface environment is much more complex than the near-earth orbit: the day-night temperature difference is as high as 300℃, the temperature in the direct sunlight area during the day rises to 127℃, and at night it drops to -173℃; at the same time, the lunar surface lacks atmospheric buffer, which not only aggravates the influence of heat conduction and radiation, but also needs to cope with high-speed micro-meteorite impact and strong solar spectrum radiation. These extreme conditions have put forward requirements far beyond existing technologies for the performance of thermal insulation materials, such as "low thermal conductivity, high reflection, lightweight, impact resistance, and cycle resistance".
[0003] At present, the technical exploration of the industry for lunar building thermal insulation mainly focuses on several types of materials, but due to the limitations of the characteristics and process level of the materials themselves, there are obvious deficiencies, which are difficult to meet the actual application requirements: One type is metal multilayer insulation (MLI), which is a commonly used thermal insulation scheme for near-earth orbit spacecraft (such as satellites and space stations). The core structure is an alternating stack of aluminized polyester film and glass fiber mesh. Although the solar spectrum reflectivity of existing MLI is relatively high, it seems to be able to cope with the radiation problem, but in the lunar high-vacuum environment, the glass fiber mesh is easily displaced due to long-term thermal cycling or launch vibration, resulting in adhesion between the film layers; once adhesion occurs, the thermal conductivity will increase significantly, and the reflective film at the adhesion site is prone to wrinkling, and the reflection effect decreases significantly. More importantly, in order to ensure the stability of the multilayer structure, the areal density of MLI is relatively large, far exceeding the "lightweight" goal of lunar buildings. The second type is rigid foam material, and the design idea of this type of material is to use a porous structure to suppress gas conduction, and at the same time, to use fiber reinforcement to improve structural strength. Although rigid foam material has a certain strength, its thermal conductivity is insufficient, and it is brittle and prone to cracking due to expansion differences with the building base under severe temperature differences, and it cannot withstand the long-term residence requirement. There is also a type of micro-nano porous ceramic, but its density is relatively large, far from meeting the lightweight requirement, and the preparation process is complex, making it impossible to be applied on a large scale.
[0004] In recent years, aerogel has become a research hotspot in the field of deep space thermal insulation due to its extremely low thermal conductivity, but it is still at the laboratory stage and has not formed an engineering scheme. The micro-nano porous structure of aerogel is prone to collapse and powdering under the repeated thermal cycling of the moon, and the thermal insulation performance decreases significantly; moreover, its mechanical properties are too poor, and its impact resistance is weak, and high-speed micro-meteorite impact may cause it to break, making it unable to cope with the impact risk on the lunar surface.
[0005] In general, the current lunar building thermal insulation technology either meets the thermal insulation but does not meet the lightweight, or takes into account the strength but cannot withstand the thermal cycle, and always cannot simultaneously achieve the comprehensive requirements of "low thermal conductivity, high reflection, lightweight, impact resistance and long service life", and lacks the stress compensation ability to cope with extreme temperature difference. These technical bottlenecks have become key problems restricting the normalization of lunar building construction, and a new composite thermal insulation material scheme is urgently needed to break through. SUMMARY
[0006] The purpose of the present application is to provide a composite thermal insulation material for lunar building with low thermal conductivity, high reflection, lightweight and long service life.
[0007] Another purpose of the present application is to provide a preparation method of a composite thermal insulation material for lunar building.
[0008] In order to achieve the above-mentioned purposes of the application, the following technical solutions are adopted: A composite thermal insulation material for lunar building, comprising a reflective film layer, a honeycomb core layer and an aerogel layer which are sequentially stacked from outside to inside; The reflective film layer is a polyimide film; The honeycomb core layer is combined with the aerogel layer, and the aerogel is partially embedded in the pores of the honeycomb core to form a honeycomb-aerogel integrated structure; The reflective film layer is combined at the local contact interface with the aerogel in the honeycomb core.
[0009] The chemical bonding layer is a "molecular level bonding area" formed by plasma activated chemical reaction at the local contact interface between the reflective film layer and the aerogel, and its essence is covalent bond connection, and its core value is to balance the low thermal resistance and high stability of the interface, which is one of the key designs to adapt to the extreme environment of the moon.
[0010] Further, the polyimide film is a gold-plated polyimide film, wherein the thickness of the polyimide substrate is 12.5 μm, the thickness of the gold-plated layer is 5 μm, and the purity of the gold-plated layer is ≥ 99.99%.
[0011] Further, the honeycomb core layer is an asymmetric aluminum foil honeycomb unit, and the cell size of the asymmetric aluminum foil honeycomb unit changes in a gradient along the thickness direction, gradually changing from 20 mm near the aerogel layer side to 5 mm near the reflective film layer side.
[0012] Further, the aerogel is a three-dimensional network skeleton of silica doped with 2wt% silicon carbide nanowires, which is prepared by supercritical drying method, and the pore size distribution is 10-100 nm.
[0013] Furthermore, a buffer frame is arranged around the edges of the reflective film layer, the honeycomb core layer and the aerogel layer. The buffer frame is made of titanium alloy. The buffer frame and the composite body formed by the reflective film layer, the honeycomb core layer and the aerogel layer are assembled by a tenon-and-mortise snap-fit composite connection method, and the buffer frame allows for thermal deformation displacement compensation of ±15mm.
[0014] Furthermore, a polyimide fiber mesh is added to the aerogel layer.
[0015] Furthermore, the reflective film layer is provided with a protective structure, which is a silicon carbide ceramic armor and polytetrafluoroethylene.
[0016] This application also discloses a method for preparing a composite thermal insulation material for lunar construction, comprising the following steps: (1) Preparation of reflective film: Using gold as the target material, a gradient gold plating layer is prepared by segmented sputtering process to obtain a gold-plated polyimide film, which is the reflective film. (2) Preparation of honeycomb core layer Aluminum alloy foil is pressed into asymmetric honeycomb units, and the edge nodes of the honeycomb units are welded to obtain the honeycomb core layer; (3) Preparation of aerogel layer 2 wt% silicon carbide nanowires were added to a silica sol, followed by the addition of a silane coupling agent to disperse the nanowires into a sol. A polyimide fiber mesh was laid flat at the bottom of a mold, and the nanowire dispersion sol was poured in and aged to form a wet gel. The wet coagulation and supercritical drying yielded a silica aerogel doped with silicon carbide nanowires and embedded in a polyimide fiber mesh, which is the aerogel layer. (4) Composite layer assembly: The honeycomb core layer is placed on the surface of the aerogel layer in the step, and the aerogel is pressed to embed part of the aerogel into the honeycomb pores of the honeycomb core layer to form a honeycomb-aerogel composite structure; a reflective film layer is covered on the outside of the honeycomb core layer of the honeycomb-aerogel composite structure, so that the reflective film layer and the aerogel exposed in the honeycomb pores form a local contact interface; the local contact interface is treated with plasma treatment equipment to form a chemical bonding layer, and the assembled composite body is obtained. (5) Buffer frame assembly Titanium alloy sheet is processed into a buffer frame, and an HfN coating is deposited on the outer surface of the frame by magnetron sputtering. The composite body is then embedded into the buffer frame and fixed to obtain the initial product of the composite thermal insulation material. (6) Protective structure: A low-temperature curing adhesive is used to bond silicon carbide ceramic armor to the outside of the reflective film layer; polytetrafluoroethylene emulsion is coated onto the outer surface of the reflective film layer by a spraying process, and then dried to form a low-tack polytetrafluoroethylene coating, thus obtaining a composite thermal insulation material for lunar construction.
[0017] The composite thermal insulation material of this application significantly reduces the overall thermal conductivity to achieve efficient thermal insulation through the synergistic design of the reflective film layer, honeycomb core layer and aerogel layer, as well as the matching optimization of the buffer frame and protective structure. At the same time, it efficiently reflects solar radiation with the gradient gold-plated layer, and relies on the composite structure of honeycomb core layer and aerogel to balance lightweight and resistance to radiation impact and micrometeorite impact. Combined with the displacement compensation function of the buffer frame, it resolves thermal deformation stress under extreme temperature differences. Furthermore, the stable compatibility of each layer of materials and the protective design greatly extend the service life. Finally, it forms a comprehensive thermal insulation performance that is suitable for the extreme lunar environment and balances low thermal conductivity, high reflectivity, lightweight, impact resistance, long service life and stress compensation, effectively ensuring the stability of the internal temperature of lunar buildings and meeting the needs of long-term residence. Detailed Implementation
[0018] The present application will be further illustrated by the following embodiments, but the scope of protection of the present application is not limited to the embodiments.
[0019] Example 1: Preparation of composite thermal insulation materials for lunar construction 1. Raw material preparation Raw materials: polyimide film (thickness 12.5μm, high temperature resistance >400℃), gold target (purity 99.995%), 5A06 aluminum alloy foil (thickness 75μm, tensile strength ≥310MPa), tetraethyl orthosilicate (analytical grade, purity ≥99.0%), ethanol (analytical grade), deionized water, silicon carbide nanowires (diameter 80-120nm, aspect ratio 120), silane coupling agent KH550 (industrial grade), polyimide fiber mesh (thickness 50μm, areal density 10g / m²), titanium alloy sheet (TC4, thickness 2mm), HfN target (purity 99.9%), silicon carbide ceramic armor (thickness 1mm, density 3.2g / cm³), polytetrafluoroethylene emulsion (solid content 60%), low-temperature curing adhesive (curing temperature 60℃, shear strength ≥15MPa).
[0020] 2. Preparation of the reflective film layer A 12.5 μm thick polyimide film was fixed on the stage of a magnetron sputtering instrument. The vacuum chamber was closed and evacuated to a pressure ≤ 5 × 10⁻⁶. -4 Pa, using 99.995% pure gold as the target material, employs a segmented sputtering process to prepare a gradient gold plating layer: First stage (bottom gold layer): Set sputtering power to 50W, argon flow rate to 20sccm, sputtering time to 15min to form a uniform gold layer with a thickness of 1μm. Second stage (middle gold layer): Adjust the sputtering power to 80W, maintain the argon flow rate at 20sccm, and sputter for 25min to form a gold layer with a thickness of 3μm. The third stage (top gold layer): the sputtering power is increased to 120W, the argon flow rate is 25sccm, the sputtering time is 30min, and a gold layer with a thickness of 5μm is formed. After sputtering, the film is allowed to cool naturally to room temperature, resulting in a gradient gold-plated polyimide film with a total thickness of 17.5 μm (12.5 μm polyimide substrate + 5 μm gold plating layer), which is the reflective film layer. The film has been tested and found to have a reflectivity of 96.2% for the 0.3-2.5 μm solar spectrum.
[0021] 3. Preparation of the honeycomb core layer 5A06 aluminum alloy foil (75μm thick) is placed into a custom honeycomb molding mold and asymmetric honeycomb cells with a gradient change in cell size along the thickness direction are formed by stamping process: the cell size on the side closer to the aerogel layer is 20mm, the cell size on the side closer to the reflective film layer is 5mm, and the honeycomb pore size ratio (pore size / wall thickness) is 1:8. The formed honeycomb units were fixed, and edge nodes were welded using an Nd:YAG laser. The laser power was set to 700W, the pulse width to 15ns, the welding speed to 10mm / s, and the defocusing amount to 1mm. Argon gas at a flow rate of 10L / min was introduced as a protective gas. After welding all nodes, the honeycomb core layer was obtained, with an areal density of 0.2kg / m³. 2 Its compressive strength reaches 0.8 MPa.
[0022] 4. Preparation of Aerogel Layer Weigh tetraethyl orthosilicate, ethanol, and deionized water in a volume ratio of 3:5:2, mix them, add 0.1 mol / L hydrochloric acid to adjust the pH to 2.5, place them in a 40℃ constant temperature water bath, and stir at 200 r / min for 2 h to obtain a transparent silica sol. Add 2 wt% silicon carbide nanowires to the silica sol, and 0.5 wt% silane coupling agent KH550. Place the mixture in an ultrasonic disperser, set the power to 500W, the ultrasonic time to 30min, and control the temperature to ≤30℃ during the process to obtain a uniformly dispersed nanowire dispersion sol. A 50μm thick polyimide fiber mesh was laid flat on the bottom of a cuboid mold, and nanowire dispersion sol was poured in to completely submerge the fiber mesh. The mixture was left to stand for 24 hours at 25℃ and 60% relative humidity to form a uniform wet gel. The mold containing the wet gel was placed in a supercritical drying device, and carbon dioxide was introduced as the drying medium. The pressure was set to 10 MPa, the temperature to 240 °C, and the drying time to 8 h. After drying, the material was allowed to cool naturally to room temperature. The resulting silica aerogel, which is doped with silicon carbide nanowires and embedded with polyimide fiber mesh, was then removed. This aerogel layer has a pore size distribution of 10-100 nm and a thermal conductivity of 0.017 W / (m·K).
[0023] 5. Composite layer assembly The prepared honeycomb core layer was laid flat on the surface of the aerogel layer, and a flatbed press was used to gently press it with a pressure of 0.2 MPa for 30 seconds, so that the aerogel part was embedded in the honeycomb pores of the honeycomb core layer, forming a tightly bonded honeycomb-aerogel composite structure. The prepared reflective film (gold plating facing out) was applied to the outside of the honeycomb core layer of the honeycomb-aerogel composite structure to ensure that the reflective film and the exposed aerogel inside the honeycomb pores formed a local contact interface. The mixture was placed in a plasma treatment machine (model: Diener Zepto W6), and argon gas was introduced as the working gas. The power was set to 300W, the pressure to 5Pa, and the treatment distance to 10mm. The local contact interface between the reflective film and the aerogel was treated for 30s to form a chemical bond layer with a thickness of about 80nm. After removal, the composite matrix was obtained.
[0024] 6. Buffer frame assembly A CNC cutting machine tool is used to process TC4 titanium alloy sheet into a rectangular buffer frame with a frame width of 50mm and a height consistent with the composite body. The frame has a tenon and mortise structure groove reserved on the inner side. The buffer frame was fixed inside the magnetron sputtering instrument. HfN was used as the target material, and the sputtering power was set to 150W, the argon flow rate to 30sccm, and the vacuum degree to 2×10⁻⁶. -4 Pa, deposit a 50 μm thick HfN coating on the outer surface of the frame by vapor deposition; The obtained composite body is embedded into the buffer frame through a mortise and tenon structure, and is fastened with GH4169 high-temperature alloy buckles with a pre-tightening force of 80N. Then, a titanium alloy pin with a diameter of 3mm is inserted to form a secondary lock, thus obtaining the initial product of the composite thermal insulation material. The thermal deformation displacement compensation of the buffer frame is tested to reach ±15mm.
[0025] 7. Protective Structure Setup Using a scraper, a low-temperature curing adhesive is evenly applied to the bonding surface of the silicon carbide ceramic armor (coating thickness 0.1mm), and then it is adhered to the outside of the reflective film layer of the composite heat insulation material. The gap between the ceramic armor joints is ≤2mm. The mixture is then placed in a 60℃ oven for 2 hours to cure, so that the ceramic armor and the reflective film layer are tightly bonded. The polytetrafluoroethylene emulsion was diluted with deionized water to a solid content of 30%, and then uniformly coated onto the outer surface of the reflective film layer, including the gaps between the ceramic armor joints, using an air spraying device. The coating thickness was controlled to be 10 μm. The emulsion was then placed in a 120°C oven and dried for 30 minutes to form a low-viscosity polytetrafluoroethylene coating, ultimately yielding a composite thermal insulation material for lunar construction.
[0026] Example 2: Performance Testing of Composite Thermal Insulation Materials The composite thermal insulation material prepared in Example 1 was subjected to extreme environment adaptability tests. The test items and results are as follows: 1. Basic performance testing: Surface density: measured by weighing method, the result is 0.82 kg / m³. 2 It meets the lightweight requirements (<0.85kg / m²). Thermal conductivity: Using the hot wire method in a vacuum environment (10) -5 The thermal conductivity was measured at Pa and the result was 0.017 W / (m·K), which is significantly lower than that of existing technologies (the thermal conductivity of traditional MLI is about 0.025 W / (m·K)). Solar spectral reflectance: The 0.3-2.5μm band was measured using an ultraviolet-visible-near-infrared spectrophotometer, and the result was 96.2%, which can effectively block the input of solar radiation heat.
[0027] 2. Mechanical property testing: Impact resistance: Simulating the mechanical environment during the launch phase, an impact test with 10G acceleration (axial, pulse width 20ms) was conducted. After the test, the material did not crack or delaminate, and the connection between the buffer frame and the composite body was stable. Resistance to micrometeorite impact: A 1mm diameter aluminum projectile (velocity 5km / s, kinetic energy approximately 60J) was fired from a two-stage light gas gun and impacted the material surface. The results showed that the silicon carbide ceramic armor successfully blocked the projectile, and the reflective film and internal structure remained undamaged.
[0028] 3. Extreme environment resistance performance test: Thermal cycling stability: Simulating lunar day-night temperature difference (-173℃ for 12h → 127℃ for 12h, heating and cooling rate 5℃ / min), 200 thermal cycling tests were conducted. After the test, the thermal conductivity change rate was <3%, the reflectivity attenuation was <2%, and there was no pulverization or cracking. Radiation stability: After 100 kGy dose of gamma ray radiation, the material's mechanical properties were retained by more than 90%, the HfN coating on the buffer frame did not peel off, and the displacement compensation function was normal. Moon dust resistance: A scouring test was conducted using simulated moon dust (SiO2 powder, particle size <100μm) (flow rate 10m / s, time 100h). The adhesion of moon dust to the PTFE coating surface was reduced by 75%, and it could be removed by slight wiping. The reflectivity attenuation was <4%.
[0029] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit it. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A composite thermal insulation material for lunar construction, characterized by, The reflective film layer, the honeycomb core layer and the aerogel layer are sequentially stacked from outside to inside. The reflective film layer is a polyimide film. The honeycomb core layer and the aerogel layer are combined, and the aerogel is partially embedded in the pores of the honeycomb core to form a honeycomb-aerogel integrated structure. The reflective film layer is combined with the local contact interface of the aerogel in the honeycomb core.
2. A composite thermal insulation material for lunar construction according to claim 1, wherein The polyimide film is a gold-plated polyimide film, wherein the thickness of the polyimide substrate is 12.5 μm, the thickness of the gold-plated layer is 5 μm, and the purity of the gold-plated layer is ≥99.99%.
3. A composite thermal insulation material for lunar construction according to claim 1, wherein The honeycomb core layer is an asymmetric aluminum foil honeycomb unit, and the cell size of the asymmetric aluminum foil honeycomb unit changes in a gradient along the thickness direction, gradually changing from 20 mm near the aerogel layer side to 5 mm near the reflective film layer side.
4. A composite thermal insulation material for lunar construction according to claim 1, wherein The aerogel is a three-dimensional network framework of silica doped with 2wt% silicon carbide nanowires, prepared by supercritical drying, and the pore size distribution is 10-100 nm.
5. A composite thermal insulation material for lunar construction according to claim 1, wherein A buffer frame is arranged around the edges of the reflective film layer, the honeycomb core layer and the aerogel layer, the buffer frame is made of titanium alloy, the buffer frame and the composite main body composed of the reflective film layer, the honeycomb core layer and the aerogel layer are assembled by a mortise and tenon-buckle composite connection method, and the buffer frame allows a thermal deformation displacement compensation of ±15 mm.
6. A composite thermal insulation material for lunar construction according to claim 1, wherein Polyimide fiber mesh is added to the aerogel layer.
7. A composite thermal insulation material for lunar construction according to claim 1, wherein The reflective film layer is provided with a protective structure, which is a silicon carbide ceramic armor and polytetrafluoroethylene.
8. A method for the production of a composite thermal insulation material for lunar construction according to any one of claims 1 to 7, characterized in that, The method comprises the following steps: (1) Preparing the reflective film layer: using gold as the target material, a gradient gold-plated layer is prepared by a segmented sputtering process to obtain a gold-plated polyimide film, which is the reflective film layer; (2) Preparing the honeycomb core layer An aluminum alloy foil is pressed into an asymmetric honeycomb unit, and the edge nodes of the honeycomb unit are welded to obtain the honeycomb core layer; (3) Preparing the aerogel layer 2wt% silicon carbide nanowires are added to the silica sol, and then silane coupling agent is added to obtain a nanowire dispersion sol; The polyimide fiber mesh is laid on the bottom of the mold, the nanowire dispersion sol is poured, and the wet gel is aged to form a wet gel; the wet gel is supercritically dried to obtain a silica aerogel doped with silicon carbide nanowires and embedded in the polyimide fiber mesh, which is the aerogel layer; (4) Composite layer assembly The honeycomb core layer is placed on the surface of the aerogel layer, and the aerogel is partially embedded in the honeycomb holes of the honeycomb core layer by pressing to form a honeycomb-aerogel composite structure; the reflective film layer is covered on the outside of the honeycomb core layer of the honeycomb-aerogel composite structure to form a local contact interface between the reflective film layer and the exposed aerogel in the honeycomb holes; the local contact interface is treated by a plasma treatment device to form a chemical bonding layer, and a composite main body is obtained; (5) Buffer frame assembly Titanium alloy plates are processed into buffer frames, and HfN coating is evaporated on the outer surface of the frames by a magnetron sputtering process; the composite main body is embedded in the buffer frame and fixed to obtain a composite thermal insulation material; (6) Protective structure The silicon carbide ceramic armor is pasted on the outside of the reflective film layer by using a low-temperature curing adhesive; the polytetrafluoroethylene emulsion is coated on the outer surface of the reflective film layer by a spraying process, and is dried to form a polytetrafluoroethylene low-adhesion coating, thereby obtaining a composite thermal insulation material for lunar buildings.